Development of an in vivo model of laryngeal burn injury. (16th June 2016) - Dion, Gregory R.; Teng, Stephanie; Bing, Renjie; Hiwatashi, Nao; Amin, Milan R.; Branski, Ryan C.
Abstract : Objectives/Hypothesis: Inhalation injury significantly increases morbidity and mortality in burn patients. Approximately one in five burn patients have acute injury to the larynx, trachea, and/or lungs—and as many as 70% have long‐term laryngeal abnormalities. Although inhalation injury to the lung has been studied extensively, no models exist to study these insults to the larynx. As such, we developed an in vivo rabbit model to create precise and reproducible laryngeal burn with resultant tissue damage as a foundation for interventional studies. Methods: Following tubeless tracheotomy, a custom temperature‐control device was employed to apply heated air (70°C–80°C, 150°C–160°C, or 310°C–320°C) ± smoke derived from unbleached cotton to the larynx, endoscopically, minimizing adjacent tissue damage in six rabbits. Pain, nutrition, and level of activity were monitored. Direct laryngoscopy and histological examination were performed 24 hours following insult. Results: All animals survived injury with appropriate pain control; oral intake was initiated and all were adequately ventilating via tracheostomy. Burn sequelae were noted under direct visualization 24 hours after injury, and graded levels of edema and tissue damage were observed as a function of temperature. Edema obstructed true vocal fold visualization at increased temperatures. These injury patterns correlated with graded tissue damage on histology. Conclusion: We created an in vivo model of laryngeal burn injury employing a custom burn device resulting in graded tissue injury. This model is critical for investigation of the mechanisms underlying burn injury, and ultimately, the development and evaluation of therapies for this challenging population. Level of Evidence: NA Laryngoscope, 127:186–190, 2017